Case Report of Tc-99m Sulfur Colloid Single-Photon Emission Computed Tomography/Computed Tomography Study Differentiating Tumor from Accessory Spleen - Reena Aggarwal; Thomas Wagner; Shaunak Navalkissoor (World Journal of Nuclear Medicine)
We present a case report where Tc-99m sulfur colloid single-photon emission computed tomography (SPECT)/computed tomography (CT) scan was useful in characterizing a soft tissue abdominal mass and helped with patient management. A 63-year-old male with no previous history of trauma had an incidental finding of a soft tissue nodule adjacent to the splenic hilum, unchanged in size over 4 months and with similar enhancing features as the spleen. A Tc-99m sulfur colloid SPECT/CT scan was performed to determine the nature of the nodule. It showed no uptake of tracer within this mass, therefore excluding splenic tissue. This prompted subsequent investigations and this tissue was found to represent a pancreatic neuroendocrine tumor, which was excised.